Teacher Education in Florida, 1968-1978. Report of the Role and Scope Task Force on Teacher Education - State Univ. System of Florida, Tallahassee; State Univ. System of Florida, Tallahassee ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
This report, which identifies problems and needs of teacher education in Florida through 1978, is the product of a 3-year task force created to explore the educational manpower needs and to study the present potential capacity of the State University System for meeting these needs. Chapter 1, which discusses the broad context of the new technology and the teacher's changing role, outlines the State University System's mission to develop and disseminate teaching technology while maintaining quality control of training program. Chapter 2 surveys the supply of teachers, source of supply, comparison with national supply, continuing and inservice needs, and other facts relative to staffing of Florida's public schools from kindergarten through junior college. Chapter 3 surveys teacher preparation programs currently available or in planning stages in the various state certification categories in each of the seven state universities. Surveyed also for each university are instructional personnel and students, classroom and laboratory space, library space and resources, supplementary facilities and personnel, and resources needed. Chapter 4 presents a proposed model for the design and evaluation of teacher training programs and recommends a plan for establishing it through a state teacher education research and development program. Chapter 5 lists the specific recommendations identified as most urgent. Appendixes contain numerous supplementary data tables. (JS)
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Faculty; Elementary School Teachers; Models; Program Design; Program Evaluation; Secondary School Teachers; Two Year Colleges; Educational Needs; Educational Resources; State Universities; Teacher Supply and Demand